PENYIMPANGAN PRINSIP KERJA SAMA DAN PRINSIP KESOPANAN WACANA KARTUN PADA BUKU POLITIK SANTUN DALAM KARTUN KARYA MUHAMMAD MICE MISRAD - Yunitawati, Azizah Malikha; Ngalim, Abdul; Sabardila, Atiqa (Universitas Muhammadiyah Surakarta, 2014)
This study deals with the violation of cooperative politeness principle of cartoon discourse found in Politik Santun Dalam Kartun by Misrad. The objectives of the study are as follows: (1) to identify the violation of cooperative principle; (2) to describe the violation of politeness principle; and (3) to describe the pedagogical implication in learning Indonesian language at vocational high school. This is a qualitative research. The data in the form of words, sentences, and discourse both monologues and dialogues containing violation of cooperative and politeness principle. Technique of collecting data used is documentation and technique of data analysis used is comparison and contrast technique. The results are as follows: (1) there are three types of violation of cooperative principles, namely: maxim of quantity, relevance, and manner. The violation of quantity maxim is dominant; (2) the violation of politeness principle covers six types, namely: tact maxim, generosity maxim, approbation maxim, modesty maxim, agreement maxim, and sympath maxim.